Optical properties of thin gold film - Kovalenko, S.A.; Fedorovych, R.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Results of studing optical constants of thin gold films are given. The values of refraction and extinction coefficients (n, æ, respectively) are calculated from reflection and transmission spectra accordingly to traditional formulae, and using new theory as well. The comparison of the results obtained by both means was held, and possible causes of divergences were considered.